Quality of life and depression among chronic kidney disease patients: a tertiary care center cross-sectional study - Nablawi, Rana A.; Alghamdi, Lama S.; Alshaikh, Adnan E.; Alagha, Abdullah M.; Alharbi, Nada T.; Ali, Abdulah H.; Khafaji, Hassan A.; Zarei, Essam W. E; Alzahrani, Nabil A. (Frontiers in Nephrology, 2025)
BackgroundChronic kidney disease (CKD) is a severe health condition that involves a decline in kidney function, leading to high mortality rates in Saudi Arabia and globally. It often coexists with chronic non-communicable conditions such as hypertension and diabetes. As CKD progresses, patients experience psychological distress, anxiety, and depression, which can negatively impact their health and quality of life. This can lead to reduced treatment adherence, increased mortality, and poor quality of life.ObjectiveThis study sought to assess the prevalence of depression among CKD patients, investigate how quality of life (QoL) and depression vary across CKD stages, and examine the relationship between depression and QoL at different disease stages. This study was conducted at a tertiary care center in Jeddah, Saudi Arabia.MethodsThis cross-sectional research, conducted in Jeddah, Saudi Arabia, from February to May 2024, included 95 CKD patients who met the CKD diagnostic criteria as confirmed by a nephrologist. Pregnant women, dialysis patients, and patients under the age of 18 were excluded from the research. Patients’ contact information was gathered from electronic medical records at King Abdulaziz University Hospital (KAUH), and consent was sought over the phone. Depression was assessed in non-dialysis CKD patients using the Patient Health Questionnaire (PHQ-9), and health-related quality of life (HRQoL) was assessed using the 12-Item Short-Form Health Survey (SF-12) score. Demographic information, previous medical comorbidities, and estimated glomerular filtration rate (eGFR) were also considered. The 2012 Kidney Disease: Improving Global Outcomes (KDIGO) CKD classification was used to classify patients into stages. The research sought to give a full evaluation of patients’ mental and physical health.ResultsA total of 95 patients were included in this study, with a predominance of male gender (58.9%) and those who were aged 60 years and above (50.5%). Most patients were non-smokers (78.9%), and 45.3% were classified as non-obese patients. Comorbidities were widespread among these patients, especially hypertension (82.1%) and diabetes (74.7%). Regarding severity level measured by PHQ-9, the median score was 12.0, 28.4% of the patients were classified as having moderate depression, and the correlation between depression and physical activity (PCS12) and mental health (MCS12) was significantly negative. Multiple linear regression analysis showed that depression was significantly associated with lower physical and mental capacity scores, alongside older age and female gender.ConclusionThis study emphasized the substantial impact of depressive symptoms among obese patients, highlighting the interplay between mental health and chronic physical conditions. Our findings suggest that specific risk factors such as fatigue, chronic illness, including hypertension, and prior mental health history are associated with increased vulnerability to depression. These insights underscore the importance of integrating routine mental health screening and individualized intervention strategies into patient care, particularly for those with comorbid conditions. Future research is needed to further explore the causal relationships and to inform more effective, targeted public health.